PENGARUH MODEL PEMBELAJARAN RESOURCE BASED LEARNING TERHADAP HASIL BELAJAR IPA PADA SISWA - Agung Velayati Syam; Amrah; Sahabuddin, Erma Suryani (Jurnal Riset Guru Indonesia, 2024)
This study aims to determine the description of the Resource Based Learning (RBL) learning model in science subjects in Class V UPT SPF SDN Mangkura V Makassar City. This study is a type of quantitative research with a pre-experimental research design. The sampling technique used is Purposive Sampling with a sample size of 36 students. The results of the descriptive statistical analysis show that the students' initial test scores (pretest) are with an average of 49.44 (in the less category) and have increased after being given treatment (posttest) with an average of 71.66 (in the good category). The results of the Sample T-test statistical analysis show Sig (2-tailed) <0.05 (0.000 <0.05) so that H0 is rejected and H1 is accepted, which means that there is a difference in science learning outcomes of class V UPT SPF SDN Mangkura V Makassar City students between before and after using the resource based learning model. So it is concluded that the Resource Based Learning learning model has an effect on the science learning outcomes of class V students of UPT SPF SDN Mangkura V Makassar City.